AGN contamination of galaxy-cluster thermal X-ray emission: predictions for eRosita from cosmological simulations. Issue 2 (6th September 2018) - Biffi, V; Dolag, K; Merloni, A
ABSTRACT: In this study, we present a modelling of the X-ray emission from the simulated supermassive black holes within the cosmological hydrodynamical Magneticum Pathfinder Simulation, in order to study the statistical properties of the resulting X-ray active galactic nuclei (AGN) population and their expected contribution to the X-ray flux from galaxy clusters. The simulations reproduce the evolution of the observed unabsorbed AGN bolometric luminosity functions (LFs) up to redshift z ∼ 2, consistently with previous works. Furthermore, we study the evolution of the LFs in the soft (SXR) and hard (HXR) X-ray bands by means of synthetic X-ray data generated with the PHOX simulator, which includes an observationally motivated modelling of an intrinsic absorption component, mimicking the torus around the AGN. The reconstructed SXR and HXR AGN LFs present a remarkable agreement with observational data up to z ∼ 2 when an additional obscuration fraction for Compton-thick AGN is assumed, although a discrepancy still exists for the SXR LF at z = 2.3. With this approach, we also generate full eROSITA mock observations to predict the level of contamination due to AGN of the intracluster medium (ICM) X-ray emission, which can affect cluster detection especially at high redshifts. We find that, at z ∼ 1–1.5, for 20–40 per cent of the clusters with M_5003× 10^13 h^-1 M_, the AGN counts in the observed SXR band exceed by more than a factor of 2 the counts from the whole ICM.